Problematika Dan Solusi Krisis Lingkungan Perspektif Al-Qur’an - Rusnatun Rusnatun (STAIFAS-Press, 2020)
The frequency of the environment (ecology) is one of the issues that is always interesting to study and discuss, the environmental damage that is happening a lot nowadays, refer to us how much set of problems that must be overcome by the government in tackling it. Forest fires in Sumatra and Kalimantan and the handling of rubbish that is still a mess in several regions in Indonesia, causing floods and environmental pollutions, that is evidence of the many problems and environmental crises in our country. These environmental crises, scientifically-philosophically is called as ecological crises, are a reflection of the spiritual crisis of modern humans that has eliminated God in relation to nature. Islam has far made the environment as an ecosystem that must always be maintained its existence, caring for and guarding it is our duty as humans, as offered by the monism theory that the true nature of the origin of all this reality is only one (all is one), in other words when we destroy nature as well as damage ourselves. Therefore, the purpose of this research is to find out the problems of environmental crises and to find out what solutions can be offered to overcome the problems of environmental crises and how ethical principles respond to environmental crises perspective of the Qur'an.